Membangun Kepercayaan dan Solidaritas Sosial dalam Ruang Madani Sebelum dan Sesudah Konflik Etnis Terjadi di Maluku - Makaruku, Nathalia Debby; Ramdhan, Rizki Muhammad (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
This research aims to provide a sociological description and analysis toward the civil sphere of the Taniwel Timur community. Social trust and solidarity became the focus to see peace maintained before and after ethnic conflicts in Maluku. There are two main important points which are, the social life of the Taniwel Timur people before and after the conflict and the way they built trust and social solidarity. This research uses qualitative methods through interview techniques with key informants, observations, and literature studies. The result of the research found that the Taniwel Timur community creates civic space through everyday relationships and interactions that remain guided by collective experiences, ways of life, traditions and habits, and social networks. In the civil sphere of the Taniwel Timur community, social trust and solidarity are built and become a resource to maintain peace when conflicts occur in Maluku.